(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Lithium cobalt nickel oxide cathodes had been doped with various metals in recent years to obtain a competitive high performance cathode material for lithium-ion batteries. Cathodes doped with Al and Mg were synthesized by solid-state reaction method. Structural investigation of this material was done using XRD. Â Galvanostatic charge/discharge and cyclic voltammetry were studied in order to outline the electrical performance of LiCo0.7Ni0.2Al0.09Mg0.01O2, LiCo0.7Ni0.2Al0.06Mg0.04O2 and LiCo0.7Ni0.2Al0.03Mg0.07O2 materials in lithium-ion batteries. Electrical impedance was done on all the materials and it gave decreasing conductivities with increasing temperature. The activation energies had negative values with increased magnesium content of the material. Larger conductivity variation with temperature was seen in the material with the higher magnesium content. Voltammographs of these materials showed good oxidation and reduction loops. Charge/discharge curve for LiCo0.7Ni0.2Al0.09Mg0.01O2 material showed about 96 mAh/g of discharge capacity for the first cycle.Â Â